FEMALE STUDENTS ACCESS TO TECHNOLOGY FOR LEARNING AND THE ATTAINMENT OF SDG-5 - Oladele, Jumoke (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study adopts a quantitative approach for evaluating the access of female students to technology engagements while learning. The population of the study were university undergraduates, while the target population were female students. Therefore, the respondents of the study were female teacher trainees. A questionnaire was designed, which was validated to ensure its appropriateness for use. Also, a Cronbach’s alpha coefficient of 0.7 was obtained which revealed that the findings reveal that while showed that the instrument was reliable. Findings revealed that female students were highly engaged in the use of technology for educational purposes. However, ease of use of digital learning platforms, technical support, peer influence, instructor support and accessibility are key factors in their decision to use digital learning platforms for learning. Also, digital learning platforms enhance the students' learning experience, while encouraging self-paced learning among others, which formed the basis of the conclusion of the study. As such, emphasising the need for targeted strategies that foster an inclusive digital environment and bridge the technology access gap remains germane to progressive access.